Implementasi Role Playing dalam Meningkatkan Kepercayaan Diri pada Mata Pelajaran PAI Kelas 1 di Sekolah SDIT Nabawi - Alfian Khadafi; Siti Qomariyah; Doa Fajarwati (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Students have low confidence in PAI learning can be seen from the symptoms that look like hesitant while speaking in front of the class and silence when appointed Master to move forward in the front of the class. The confidence of manifests is comfortable in the environment where the individual is so that individuals feel confident of a step and decision he takes to achieve its expected goals. Confidence is necessary to students to create a good learning attitude so that it can achieve optimal learning achievement. To answer this, the Role Playing model is to complete it, the implementation of the Role Playing learning model in increasing confidence, with the goal to obtain information about the level and the extent to which the Role Playing learning model can increase confidence. For research methods, researchers use descriptive qualitative methods. Interviews, observation and documentation as data collection. And Miles and Hubberman techniques as the data analysis technique, with the procedure of analysis, with the procedure 1) data collection, 2) data reduction, 3) data presentation and 4) Verification of data, as well as data inspection techniques 1) credibitiasi, 2) Tranferability and 3) The dependability as the result of this research is a learning model of role playing can increase student confidence, on the other hand the dominant students are more understandable about the material taught, given the students of elementary school 1 tend to be active and expressive so it can be said the role playing model is very relevant to the students of elementary school class. Islamic Education